Cardiovascular diseases and their risk factors - an analysis on the theme - Marluci Andrade Conceição Stipp; Alessandra Andrada de Souza; Renata Silva dos Santos (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This study is part of the first stage of an extension project entitled "The Nursing Care in Cardiovascular Diseases - Indicatives of a Healthy Life Style" from the Escola de Enfermagem Anna Nery of the Federal University of Rio de Janeiro. Its objective is to identify scientific production concerning the cardiovascular diseases and its risk factors. It is a bibliographical study whose data investigation was carried out through a research in the Virtual Library of Health. The database was taken from the Caribbean and Latin American Literature Health Sciences (LILACS). Nursing manuscripts from 2001 to 2006 referring to qualis international B and C, have been analysed. The keywords were: cardiovascular diseases, life style, risk factors and nursing, having a total of 1576 articles been found. Results showed that in those articles, 3.5% mentioned some type of cardiovascular risk. The Latin American Journal of Nursing from the University of São Paulo was the manuscript the mostly focused on that theme. As for the periodicals that approach cardiovascular diseases and life style, the percentage is only 0.2% and 0.4% respectively, confirming the real need for research of the nursing professionals on this theme. The cardiovascular problems are presented as an important problem of public health and the nurse has the main responsibility for the activities of education in health, coordination and control of the assistance that aims at adequate change of life style, treatment and appropriate self-care